1991
DOI: 10.2134/agronj1991.00021962008300040005x
|View full text |Cite
|
Sign up to set email alerts
|

Summer Patch and Kentucky Bluegrass Quality as Influenced by Cultural Practices

Abstract: Summer patch, caused by Magnaporthe poae Landschoot and Jackson, is among the most destructive diseases of Kentucky bluegrass (Poa pratensis L.). While fungicides may reduce disease severity, information regarding the impact of cultural practices on this disease is unavailable. Hence, the objectives of this field investigation were to examine the effect of irrigation practice [light frequent (LF) versus deep infrequent (DI) irrigation); mowing height (3.8 versus 7.6 cm); and N source (urea, sulfur coated urea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Such research is likely the next step in investigating control of root diseases with antifungal compounds. Before 1984, all patch diseases with similar symptoms to summer patch were described as Fusarium blight (Davis and Dernoeden, 1991). Smiley and Fowler (1984) then described a separate pathogen, Phialophora graminicola, to be the causal agent of the summer patch disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such research is likely the next step in investigating control of root diseases with antifungal compounds. Before 1984, all patch diseases with similar symptoms to summer patch were described as Fusarium blight (Davis and Dernoeden, 1991). Smiley and Fowler (1984) then described a separate pathogen, Phialophora graminicola, to be the causal agent of the summer patch disease.…”
Section: Discussionmentioning
confidence: 99%
“…Turgeon (1991) stated that lower mowing heights result in aesthetically more pleasing turfs but also reduce the turfs defenses against environmental and disease pressures. Davis and Dernoeden (1991) found that summer patch damage was less severe in Kentucky bluegrass turf maintained at 7.6 cm versus turf maintained at 3.8 cm. Susceptibility of plants to M. poae (reported as Phialophora graminicola) was more pronounced in turf mown at 2 cm versus unmowed (Smiley et al, 1985).…”
Section: B2 Summer Patch Controlmentioning
confidence: 92%
See 2 more Smart Citations
“…Small increases in cutting height have proven beneficial in reducing anthracnose severity; Inguagiato et al (2008) previously reported that mowing annual bluegrass at 3.6 mm reduced anthracnose disease up to 21% compared to mowing at 3.2 and 2.8 mm. Removing less leaf tissue could enhance the photosynthetic capacity of the turf sward, thus allowing for greater carbohydrate storage, better plant health and increased disease suppression (Younger, 1969); increased defoliation resulting from low mowing heights in Kentucky bluegrass ( Poa pratensis L.) decreased total nonstructural carbohydrates and increased summer patch disease (Davis and Dernoeden, 1991).…”
Section: Discussionmentioning
confidence: 99%